Thinking Outside the Block: Projected Phases of Blockchain Integration in the Accounting Industry. Issue 2 (15th January 2019) - Karajovic, Maria; Kim, Henry M.; Laskowski, Marek
Abstract: This paper aims to propound a thorough and circumspect analysis of the implications of blockchain technology in the accounting profession and its broader industry. The analysis begins with a summary of early developments by first movers and how they are harnessing blockchain technology to improve business practices. Concomitantly, the paper will go on to discuss how this technology will streamline accounting processes, specifically as the technology approaches critical mass. Finally, a discussion of its long‐term implications will follow through a more philosophical and conceptual dialogue. Throughout the paper, criticisms will be raised to address concerns regarding blockchain's widespread use. Abstract : This paper critically examines the implications of blockchain technology in the accounting industry. It studies early developments by first movers and explicates how the technology will streamline accounting processes in areas of bookkeeping, audit and taxation as the technology approaches critical mass. of the paper also discusses its long‐term implications.